2016
DOI: 10.1140/epje/i2016-16006-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viscoelasticity on droplet dynamics and break-up in microfluidic T-Junctions: a lattice Boltzmann study

Abstract: Abstract. The effects of viscoelasticity on the dynamics and break-up of fluid threads in microfluidic T-junctions are investigated using numerical simulations of dilute polymer solutions at changing the Capillary number (Ca), i.e. at changing the balance between the viscous forces and the surface tension at the interface, up to Ca ≈ 3 × 10 −2 . A NavierStokes (NS) description of the solvent based on the lattice Boltzmann models (LBM) is here coupled to constitutive equations for finite extensible non-linear e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
(211 reference statements)
0
5
0
Order By: Relevance
“…[53], where it is shown that the LBM are actually able to capture sizable effects of non-Newtonian rheology on the droplet formation process. The present numerical work follows other studies by some of the authors [30,[54][55][56][57], where a NS description based on LBM has been coupled to constitutive equations for different polymer dynamics. Specifically, in two recent papers [54,55], three-dimensional (3D) simulations are carried out to quantify the effects of elasticity in the breakup processes in confined T-junctions [54] and cross-junctions [55], and to investigate the effects of thinning [30] in open microfluidic geometries [58,59].…”
Section: B Numerical Simulationsmentioning
confidence: 94%
See 1 more Smart Citation
“…[53], where it is shown that the LBM are actually able to capture sizable effects of non-Newtonian rheology on the droplet formation process. The present numerical work follows other studies by some of the authors [30,[54][55][56][57], where a NS description based on LBM has been coupled to constitutive equations for different polymer dynamics. Specifically, in two recent papers [54,55], three-dimensional (3D) simulations are carried out to quantify the effects of elasticity in the breakup processes in confined T-junctions [54] and cross-junctions [55], and to investigate the effects of thinning [30] in open microfluidic geometries [58,59].…”
Section: B Numerical Simulationsmentioning
confidence: 94%
“…Here the focus is instead on thinning effects in the T-junction geometry. We refer the interested reader to our previous papers where all the relevant LBM technical details are discussed [30,[54][55][56]. In Sec.…”
Section: B Numerical Simulationsmentioning
confidence: 99%
“…The viscous pressure drop across each globule, and thus its ability to be displaced and recovered, is thus reduced. Due to their extensional viscosity, polymers are thought to suppress this breakup process-as shown in idealized experiments and simulations [201][202][203][204] -and thereby improve non-aqueous fluid recovery. Experiments on bulk rock cores show indirect agreement.…”
Section: Improved Fluid Recovery From Porous Mediamentioning
confidence: 99%
“…The code has been extensively used and validated in the past by several groups to study: droplet deformation and breakup (Gupta, Sbragaglia & Scagliarini 2015), also in association with thermocapillary (Gupta et al. 2016) and viscoelastic (Gupta & Sbragaglia 2016) effects; droplet formation in microfluidic devices (Chiarello et al. 2017); sliding droplets (Varagnolo et al.…”
Section: Methodsmentioning
confidence: 99%